Calculating position and velocity vectors of GLONASS satellites from broadcast ephemeris and aspects related to its integration with GPS - Statella, Thiago; Aguiar, Claudinei R.; Monico, João F. G. [UNESP]; Nogueira, José R. [UNESP] (Universidade Federal do Rio Grande do Sul, 2013)
This paper presents details on the estimation of position and velocity vectors for GLONASS satellites from their broadcasted ephemeris using forth-order Runge-Kutta integration method and deals with the compatibility between GLONASS ephemeris and GPS time system. Besides, we analyze the compatibility between GLONASS and GPS time systems. In order to assess the quality of the integration method the coordinates calculated were compared to the broadcasted ones. The mean discrepancy was 1.33 m with a standard deviation of ±0.83 m. Next, we showed how to make GPS and GLONASS (time) systems compatible by calculating GLONASS coordinates from broadcasted ephemeris in GPS time. The results were compared to the IGS coordinates. The mean discrepancy was 6.53 m which agrees with the GLONASS broadcasted ephemeris precision.
Cálculo dos vetores de posição e velocidade dos satélites GLONASS a partir das efemérides transmitidas e aspectos relacionados à sua integração com o GPS
Keywords: GLONASS; GPS; Numeric integration; Orbits; Runge-Kutta